GOOD REGULATION AND THE PRINCIPLE OF ECONOMIC FREEDOM IN THE CASE OF EUROPEAN INSURANCE LAW - Grzeszczak, Robert; Klemt, Tomasz (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2020)
The authors put forward the thesis that the European regulator’s activity can be assessed in the context of the criteria of good regulation (in each of their dimensions). This is due in particular to the form and content of the legislative process in the European Union. They analyze the Directive (EU) 2016/97 (hereinafter: ‘the Insurance Distribution Directive’ or ‘IDD’) in the context of its quality per se, the legislative process and the intended objective of preventing misseling, while assessing its impact on economic freedom. The first objective of the paper is to discuss the hypothesis that 21st century is the time of transition from government to governance, which is connected with the postulate of the necessity of good governance in the European Union (hereinafter: ‘EU’) and in the Member States. The second objective of this paper is to discuss the analytical issues related with the very concept of good regulation in the EU and its impact on economic freedom. The next objective of this paper is to evaluate the selected legal act (IDD) in terms of criteria of Better Regulation for Better Results to show the practice dimension of European Insurance Law regulation.